(untitled) (Swiss Medical Weekly, 2021)
OBJECTIVES: To compare consultations at the Otorhinolaryngological Department at a tertiary referral centre between the COVID-19 lockdown in 2020 and the same period in 2019, as well as to study the impact of deferring visits on disease progression. METHODS: The emergency consultations during these time periods were analysed retrospectively. The effect of postponing appointments on disease progression was examined for 122 patients with chronic rhinosinusitis, for 50 patients with a benign tumour and for 22 patients with the diagnosis of a malignant tumour. To compare disease progression, patients with the diagnosis of a malignant tumour were matched to patients seen over the same period in 2019. RESULTS: During the lockdown, a reduction of 44.1% in emergency consultations compared with 2019 was observed. The largest significant decrease of consultation numbers was seen for otitis media and for Eustachian tube dysfunction. Fewer patients with tonsillitis sought emergency assistance; however, no difference in frequency of abscesses was observed. Disease progression was seen in 44.4% of patients with chronic rhinosinusitis. In 2020, 18.8% of patients with the diagnosis of a malignant tumour showed disease progression, yet no difference from the previous year was observed. CONCLUSION: Fewer emergency consultations took place during the COVID-19 lockdown; among others, there were fewer visits due to otitis media and tonsillitis. However, no change in the incidence of complications was noted. Almost 50% of patients with chronic rhinosinusitis showed disease progression, leading to prolonged suffering due to the rescheduling of appointments. The treatment of patients with the diagnosis of a malignant tumour was not affected by the postponement of consultations.